PROFESSIONAL ORIENTATION AS THE TECHNOLOGY FOR SOCIAL ADAPTATION AND REHABILITATION OF CHILDREN FROM AT-RISK GROUPS - Israilova, Nodira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article reveals the main direction of vocational counseling of children from at-risk groups using effective pedagogical technologies. Vocational counseling is considered as an important condition of professional life self-determination, successful social adaptation and rehabilitation of children in societies.